Arctic canopy photosynthetic efficiency enhanced under diffuse light, linked to a reduction in the fraction of the canopy in deep shade. Issue 4 (4th March 2014) - Williams, Mathew; Rastetter, Edward B.; Van der Pol, Laura; Shaver, Gaius R.
Summary We investigated how radiation conditions within a tundra canopy were linked to canopy photosynthesis, and how this linkage explained photosynthetic sensitivity to sky conditions, that is total radiation and its diffuse fraction. We measured within canopy radiation at leaf scales and net CO2 exchanges at canopy scales, under varied total irradiance and diffuse fraction, in Alaskan shrub tundra. Normalised mean radiation profiles within canopies showed no significant differences with varied diffuse fractions. However, radiation density distribution was non‐normal, being more unimodal under diffuse conditions and distinctly bimodal under direct sunlight. There was a nearly three‐fold increase in the proportion of the canopy in deep shade under direct illumination, compared to diffuse conditions. Under diffuse conditions the canopy had higher light‐use efficiency (LUE), resulting in up to 17% greater photosynthesis. The enhancement in LUE under diffuse illumination was not related to differences in the mean light profiles, but instead was due to significant shifts in the density distribution of light at leaf scales, in particular a reduced fraction of the canopy in deep shade under diffuse illumination. These results provide unique information for testing radiative transfer schemes in canopy models, and for better understanding canopy structure and trait variation within plant canopies.